2006
DOI: 10.1166/jnn.2006.211
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Study of Fullerene-Like WS<SUB>2</SUB>

Abstract: Inorganic fullerene-like nanoparticles of WS2 (IF-WS2), are synthesized by a reaction of tungsten oxide with molecular hydrogen and hydrogen sulfide. The synthesized nanoparticles appear as large agglomerates (>40 microns), each one counting thousands of IF nanoparticles. 1H nuclear magnetic resonance study of these nanoparticles is reported. The measurements show that the prepared product contains water (and possibly some hydrogen) molecules that occupy the voids in the central part of the fullerene-like nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The time variation of the electrical resistivity in pristine IF-WS 2 material indicates that hydrogen and water are entrapped in nanopores between the agglomerated nanoparticles and within the nanoparticles themselves [15]. Preliminary 1 H NMR measurements of the annealed sample showed that the amount of entrapped water/hydrogen molecules decreased by a factor of four in comparison with the as-prepared sample at the room temperature.…”
Section: Original Papermentioning
confidence: 98%
See 3 more Smart Citations
“…The time variation of the electrical resistivity in pristine IF-WS 2 material indicates that hydrogen and water are entrapped in nanopores between the agglomerated nanoparticles and within the nanoparticles themselves [15]. Preliminary 1 H NMR measurements of the annealed sample showed that the amount of entrapped water/hydrogen molecules decreased by a factor of four in comparison with the as-prepared sample at the room temperature.…”
Section: Original Papermentioning
confidence: 98%
“…Contrarily, the water molecules which were trapped within the core of the nanoparticles during the synthesis and removed by vacuum annealing would not be expected to readsorb in the ambient conditions. In fact, a recent 1 H NMR study [15] clearly indicated that water molecules were present in the pristine nanoparticles. This study shows that the free roation of the water molecules which are present inside the IF nanoparticles and in nanopores between the agglomerated nanoparticles was frozen out below 160 K. Note also that the water induced peak was appreciably smaller for the annealed (IF) as compared to the non-annealed samples.…”
Section: Wwwpss-bcommentioning
confidence: 99%
See 2 more Smart Citations
“…in medical devices [12]. A 1 H NMR study [13] of the IF-WS 2 nanoparticles showed that the nanoparticles entrapped water molecules, or OH groups, which were obtained as a by-product during the conversion of the oxide nanoparticles into the metal sulfide (IF) and perhaps also some residual hydrogen molecules. The water molecules are believed to be located in defects arising due to the folding of the IF-WS 2 layers.…”
Section: Introductionmentioning
confidence: 99%